Umbilical cord blood androgen levels in girls and boys assessed by gas chromatography–tandem mass spectrometry. Issue 171 (July 2017) - Lundell, Anna-Carin; Ryberg, Henrik; Vandenput, Liesbeth; Rudin, Anna; Ohlsson, Claes; Tivesten, Åsa
Highlights: DHT levels can be estimated in human umbilical cord blood by GC–MS/MS. The sex difference in DHT levels exceed that of testosterone. Gestational age at delivery associates with DHT in boys and DHEA in girls. In both sexes, DHEA, but not DHT or testosterone, associates with SHBG. Abstract: Androgen exposure of the fetus during gestation plays an important role in human physiology and pathophysiology, but assessment of androgens, in particular dihydrotestosterone (DHT), in human umbilical cord blood is technically challenging. The aim of this study was to assess umbilical cord androgen levels, including DHT, at birth by a highly sensitive assay, and study their association with sex of the infant, sex-hormone-binding globulin (SHBG) levels, and gestational age at delivery. Swedish infants (27 girls, 26 boys) were recruited at maternity care clinics in Southern Sweden. Umbilical cord blood levels of dehydroepiandrosterone (DHEA), androstenedione, testosterone and DHT at delivery were assessed by a gas chromatography–tandem mass spectrometry assay. Cord blood levels of DHT were 2.4-fold higher in boys (median 27.8 pg/mL) than in girls (11.5 pg/mL), while the sex difference was less pronounced for testosterone (1.3-fold higher in boys) and non-significant for DHEA and androstenedione. Gestational age at delivery associated inversely with DHT levels in boys and with DHEA levels in girls. There was a strong inverse correlation between SHBG and DHEA in both sexes, while there were no associations between SHBG and testosterone or DHT levels. In conclusion, using state of the art technology, we report that there is a pronounced sexual dimorphism in human umbilical cord blood DHT levels. The possibility to assess a complete androgen profile in human cord blood opens up for future increased understanding of the biological impact of the fetal androgen milieu.